The Impact of Organizational Culture on Product Innovation in Start-up Companies - Sujoko Sujoko (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2026)
Start-up companies operate in a dynamic business environment characterized by rapid technological change, market uncertainty, and intense competition, making product innovation a key prerequisite for sustainability and competitiveness. This study aims to analyze the role of organizational culture in shaping and supporting the product innovation process in start-up companies. A qualitative approach with a descriptive-exploratory design was used to gain an in-depth understanding of the values, norms, and work practices that influence innovative behavior. Data were collected through in-depth interviews with founders, team leaders, and employees, non-participatory observation of interactions and work processes, and organizational documentation studies. Data were analyzed thematically to identify patterns of relationships between organizational culture and product innovation stages. The results show that an organizational culture formed organically through intensive interaction, openness to ideas, cross-functional collaboration, tolerance for risk, and diversity of perspectives plays a significant role in driving product innovation. This culture influences all stages of innovation, from ideation to commercialization, and strengthens organizational learning and team psychological resilience. The findings also confirm that start-up sustainability and competitiveness are supported by the integration of cultural value stability and strategic flexibility. This study positions organizational culture as a strategic infrastructure that determines the effectiveness of product innovation in start-up companies.